Die opkoms en huidige stand van die Nuwe-Testamentiese ondersoek in Suid-Afrika: Deel 2 - Toit, Andries Bernardus du (Hervormde teologiese studies, 1993)
The rise and current state of New Testament research in South Africa: Part 2 The dynamic development of New Testament research since 1965 is depicted with special reference to the role of the New Testament Society of South Africa and international interaction with colleagues. The wide variety of methodological trends are discussed.